Performance of 119 Brazilian children on Stroop paradigm: Victoria version Desempenho de 119 crianças brasileiras no paradigma Stroop: versão Victoria - Helenice Charchat-Fichman; Rosinda Martins Oliveira (Arquivos de Neuro-Psiquiatria)
BACKGROUND: The Stroop paradigm evaluates susceptibility to interference and is sensitive to dysfunction in frontal lobes. Performance in the Stroop changes along the development. Despite its usefulness in research and clinical settings, there are few studies with Brazilian samples. OBJECTIVE: This study investigates the performance and age effect on Stroop paradigm of Brazilian children. METHOD: A sample of 119 children, aged from 7 to 10 years, was submitted to the Victoria version of Stroop. RESULTS: The pattern of results observed was similar to that observed in foreign studies with adults and children. Younger children were overall slower than older ones (positive correlation between age and naming time). Also, younger children showed more susceptible to interference than older ones (negative correlation between age and number of errors for the maximal interference condition). CONCLUSION: There was an age effect explained in terms of developmental changes in information processing velocity and attention selectivity. INTRODUÇÃO: O paradigma Stroop avalia a susceptibilidade à interferência e é sensível a disfunção nos lobos frontais. O desempenho no Stroop muda durante o desenvolvimento. Apesar de sua utilidade na pesquisa e na clínica, existem poucos estudos brasileiros. OBJETIVO: Investigar o desempenho e efeito de idade de crianças brasileiras no Stroop. MÉTODO: A versão Victoria do Stroop foi aplicada em 119 crianças (7 a 10 anos). RESULTADOS: O padrão de resultados observado é comparável a estudos estrangeiros com adultos e crianças. Crianças mais jovens foram mais lentas do que as mais velhas (correlação positiva entre idade e tempo de nomeação). Os mais jovens apresentaram maior susceptibilidade à interferência, comparados aos mais velhos (correlação negativa entre idade e número de erros para a condição de interferência máxima). CONCLUSÃO: O efeito de idade foi observado e discutido em termos de mudanças na velocidade de processamento da informação e na seletividade da atenção.